Sudden multiple fractures in a patient with sarcoidosis in multiple organs. (7th April 2014) - Sada, Mitsuru; Saraya, Takeshi; Ishii, Haruyuki; Goto, Hajime
Abstract : A 30-year-old man who incidentally fractured his right olecranon and other multiple phalanges was admitted to our hospital. He had a 2-year history of uveitis and bilateral hilar lymphadenopathy (BHL), and pulmonary sarcoidosis was diagnosed from transbronchial lung biopsy. Right elbow arthrodesis was performed, and biopsied specimens showed non-caseating epithelioid cell granuloma, suggesting osseous sarcoidosis. He was discharged uneventfully without further treatment, but BHL had progressed with the appearance of lung parenchymal lesions 3 months later. At that time, involvement of other organs was also noted on Gallium-67 scintigraphy, showing accumulations in BHL, axillary and inguinal lymph nodes, enlarged liver and spleen and subcutaneous areas. After initiation of steroid therapy, multiple organ involvement improved, and no further bone involvement has been recognised to date. Osseous sarcoidosis complicated by bone fracture is an extremely rare presentation, but should be considered in patients with sarcoidosis, especially when multiple organs are involved.